PENINGKATAN KOMPETENSI GURU SMP DI KABUPATEN JAYAPURA MELALUI SUPERVISI AKADEMIK BERBASIS COACHING DAN METODE BERDIFERENSIASI - Farida, Nurul; Dwikurnianingsih, Yari; Sanoto, Herry (Consilium: Education and Counseling Journal, 2024)
This research aims to examine the effectiveness of coaching-based academic supervision and differentiated methods in improving teacher competency in junior high schools in Jayapura district, Papua. Coaching-based supervision is applied to create collaborative and reflective communication between supervisors and teachers, while a differentiated approach allows supervision to be tailored to individual teacher needs. This research uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, participatory observation and open questionnaires. The research results show that the coaching approach is effective in identifying teachers' strengths and challenges and improving their skills in teaching and classroom management. The differentiated method allows for more personalized supervision, increasing teachers' self-confidence and reflective abilities. Overall, this research found that both approaches were able to create an inclusive and collaborative supervision environment, increase teacher professional competence, and form a culture of cooperation in schools. These findings support the implementation of more adaptive academic supervision in schools to improve the quality of education.